RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN KENAIKAN JABATAN DI PT.TIMOR TELECOM DENGAN MENGGUNAKAN ALGORITMA PROFILE MATCHING - Rosario, Maria Madalena Do; Marisa, Fitri; Wijaya, Indra Darma (DINAMIKA DOTCOM, 2019)
In large companies such as PT. Telkom, with a large number of employees, it is difficult to process employee appraisals by manual, because it will spend a lot of time and money. The thing that must be observed is how to choose employees in accordance with the criteria that exist in a particular position, then if there are vacant positions, it is the duty of the Human Resource Department (HRD) to conduct an assessment of each employee to fill the position. One solution for time and cost efficiency in determining the promotion of employees in an agency is to build a decision support system that uses Gap analysis. Gap is the difference between employee profile and position profile. Decision support systems using Gap analysis are made based on data and HR norms. Gap calculation process is carried out to determine employee promotion in the Job Enhancement System based on three aspects, namely knowledge and corporate culture, ability, and personality. Standard profile data, core factor mapping, and secondary factors are determined by the company. Standard profiles that are used for all sub-variables are 4 and percentage sharing for knowledge and corporate culture is 40%, ability is 30%, and personality is 30%, while division for core factors is 60% and secondary factor is 40%. Based on the results of the tests that have been carried out, the highest score is 4,395 with NIK 10201346, which means that employees with NIK 10201346 will be recommended for promotion. Keywords: Decision Support System, Profile Matching